Classification of Congestion in Jakarta Using KNN, Naïve Bayes and Decision Tree Method - Sri Rahayu; Bayu Rimbi Asmoro; Ery Rinal (Jurnal Syntax Admiration, 2023)
Congestion has now become a problem that occurs in almost all big cities in Indonesia. The problem of traffic jams generally occurs in areas with high intensity of activity and land use. Given the increasing level of congestion that is happening, the capital city of DKI Jakarta is one of the most densely populated cities with high population activity. Population activities are also offset by the use of transportation. Both by public and private vehicles. Traffic jams are one of the problems that are still unsolved. West Palmerah Street is one of the roads with quite a lot of traffic jams. To prove it, he did some simple research. The method used is descriptive method, where the research begins with collecting the data needed at this time through several surveys. And the calculation is done by looking for the degree of saturation (DS) and vehicle speed at three checkpoints, the DS at the pre-market checkpoint is 0.89, the DS at the market checkpoint is 1.05, and the DS at the market checkpoint is 0.89. Then the movement speed was also obtained at the pre-market observation point of 32.05 km/hour, at the market review point of 27.5975 km/hour, and at the post-market observation point of 33.35 km/hour. The results prove that there is indeed a traffic delay in front of the market. This figure is due to the large number of angkots that stop and the narrowing of the traffic lane in front of the market due to the presence of street vendors and motorbikes stopping on the sidewalks with buying and selling activities on the sidewalks. Therefore, it is necessary to apply the best operational solutions to improve traffic flow on these roads.